AGING NETWORK ADMINISTERED PUBLIC LONG-TERM CARE SYSTEMS-THE WASHINGTON AND OREGON MODELS. (11th November 2018) - Luo, B
Abstract: Oregon pioneered the development of publicly funded long-term care (LTC) systems administered by non-profit Aging Network organizations in the early 1980s. Washington adopted the same model a few years later. Since then both systems have become recognized as among the best public LTC systems across the nation with high levels of cost effectiveness and person centered services. The presentation will: first, describe the political and economic contexts and the key policymakers behind the creation of these two models in the 1980s; second, delineate WA's path to its success and analyze the political economic environment at the federal, state, and local levels that have allowed the system to be maintained and expanded during the past three decades; third, understand and assess the major challenges facing the WA system and the current efforts to address such challenges within the state legislature and the AN, among labor organizations, and other constituencies.